Comparative Efficacy of Rosuvastatin Monotherapy and Rosuvastatin/Ezetimibe Combination Therapy on Insulin Sensitivity and Vascular Inflammatory Response in Patients with Type 2 Diabetes Mellitus - Han, Ji Hye; Joung, Kyong Hye; Lee, Jun Choul; Kim, Ok Soon; Choung, Sorim; Kim, Ji Min; Kang, Yea Eun; Yi, Hyon-Seung; Lee, Ju Hee; Ku, Bon Jeong; Kim, Hyun Jin (Diabetes & metabolism journal, 2024)
Background: Type 2 diabetes mellitus (T2DM) induces endothelial dysfunction and inflammation, which are the main factors for atherosclerosis and cardiovascular disease. The present study aimed to compare the effects of rosuvastatin monotherapy and rosuvastatin/ezetimibe combination therapy on lipid profile, insulin sensitivity, and vascular inflammatory response in patients with T2DM.Methods: A total of 101 patients with T2DM and dyslipidemia were randomized to either rosuvastatin monotherapy (5 mg/day, n=47) or rosuvastatin/ezetimibe combination therapy (5 mg/10 mg/day, n=45) and treated for 12 weeks. Serum lipids, glucose, insulin, soluble intercellular adhesion molecule-1 (sICAM-1), and peroxiredoxin 4 (PRDX4) levels were determined before and after 12 weeks of treatment.Results: The reduction in low density lipoprotein cholesterol (LDL-C) by more than 50% from baseline after treatment was more in the combination therapy group. The serum sICAM-1 levels increased significantly in both groups, but there was no difference between the two groups. The significant changes in homeostasis model assessment of insulin resistance (HOMA-IR) and PRDX4 were confirmed only in the subgroup in which LDL-C was reduced by 50% or more in the combination therapy group. However, after adjusting for diabetes mellitus duration and hypertension, the changes in HOMA-IR and PRDX4 were not significant between the two groups.Conclusion: Although rosuvastatin/ezetimibe combination therapy had a greater LDL-C reduction effect than rosuvastatin monotherapy, it had no additional effects on insulin sensitivity and vascular inflammatory response. Further studies are needed on the effect of long-term treatment with ezetimibe on insulin sensitivity and vascular inflammatory response.